Foreign Direct Investment in Latvia and Serbia: A Comparative Analysis - Kastratović, Radovan; Krivins, Anatolijs (Comparative Economic Research. Central and Eastern Europe, 2025)
The main purpose of this study is to compare foreign direct investment (FDI) patterns in Latvia and Serbia, examining underlying trends, institutional frameworks, and historical contexts that shape investment dynamics. By analyzing regulatory structures, incentive schemes, and investment structure and dynamics, we synthesize best practices and policy recommendations for fostering sustainable investment inflows in both countries. The study employs a comparative case study approach to analyze institutional frameworks related to FDI, as well as the performance of foreign affiliates and the dynamics of FDI inflows in Latvia and Serbia, focusing on the period from 2010 to 2023. Utilizing descriptive statistical methods and data from central banks, national statistical offices, and international organizations, the research examines trends, structures, and origins of FDI, connecting them to historical contexts and institutional and economic factors. Despite their disparate historical contexts, both countries share a common thread in their transition toward market-oriented economies, marked by proactive policies aimed at attracting foreign investment. Our study shows how divergent approaches in integration and regulatory harmonization impact patterns, structures, and dynamics of foreign direct investment. Our research proposes tailoring FDI frameworks and incentive policies to leverage the strengths and address weaknesses in Latvia and Serbia. For Latvia, expanding economic diplomacy and supporting existing foreign affiliates could enhance investment retention and attraction, particularly from non-European Union (EU) countries. For Serbia, policies should prioritize FDI in technology-intensive and high-value-added sectors, supported by digitalization, workforce development, and regulatory alignment with the EU. The study provides a unique quantitative and qualitative comparison of factors that affect the FDI inflows, dynamics, and structure of those inflows in Latvia and Serbia, contributing to understanding the options of policymakers in transition economies for attracting investments and ensuring that they have positive effects on economic development.